Exploring the Status of Preference, Utilization Practices, and Challenges to Consumption of Amaranth in Kenya and Tanzania. (18th June 2022) - Nyonje, Winnie A.; Yang, Ray-Yu; Kejo, Dyness; Makokha, Anselimo O.; Owino, Willis O.; Abukutsa-Onyango, Mary O.
Abstract : African leafy vegetables such as amaranth have been utilized since time immemorial both as food and as medicine. These vegetables grew naturally in most rural environments, but currently most of them are cultivated both for home consumption and for sale. The aim of this study was to identify the most preferred amaranth species and cooking and utilization practices, as well as the beliefs and attitudes that encourage or discourage use of this vegetable. The study was carried out in seven counties of Kenya and in three regions in Tanzania. Twenty Focus Group Discussions (FGDs) with members of the community and twenty Key Informant Interviews (KIIs) with agricultural and nutrition officers were conducted in the study areas to obtain information on preferred varieties, sources of amaranth vegetables, common cooking methods, alternative uses, beliefs and taboos surrounding amaranth consumption, and the challenges experienced in production and consumption. The findings of the study showed that amaranth is one of the most commonly consumed indigenous vegetables in Kenya and Tanzania. The preference for varieties and cooking habits differs depending on the community and individuals. Amaranthus dubius and Amaranthus blitum were most common in Kenya, while Amaranthus dubius and Amaranthus hypochondriacus were most common in Tanzania. Most people consumed these vegetables because they were affordable and available or because of circumstance of lacking other foods. Regarding cooking, final taste was mostly considered rather than nutritional attribute. Several alternative uses of amaranth such as uses as medicine and livestock feed were also reported, as well as some beliefs and taboos surrounding the vegetable. Training on nutritional attributes and promotion of food preparation practices that ensure maximum nutrient benefits from amaranth is needed at the community level to realize the nutritional importance of the vegetables. Hands-on training and demonstrations were the most preferred modes of passing information.